Analisa Gambaran Post Mortem Makroskopis dan Mikroskopis Organ Jantung dan Ginjal pada Tikus Wistar Setelah Pemberian Warfarin LD50 dan LD 100 - Anggoro Adjar Mangestu; Gatot Suharto; Siti Amarwati (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Its about 800.000 people die caused of suicide in a year. In 2012, suicide is the second most common cause of death in juvenile, range of age is 15-29 yo (WHO). One of common cause in suicide is using poison, and one of them is medical drugs. Warfarin is a substance which belong to medical drug as a human therapeutic agent but also can be use as a rodenticide. This study was aimed to analyze the effect of Warfarin administration in Wistar Rats organs especially brain and liver in a macroscopic and microscopic presentation.Aim : to know macroscopic and microscopic view after the provision of warfarin a dose of LD-50 and LD-100.Method : Laboratoric experimental study with 27 male Wistar Rats divided into 3 groups. Two treatment groups were given single dose Warfarin LD-50 200mg/kg BW and Warfarin LD100 400mg/kg BW. This study was conducted in Biology Faculty UNES and Patology Anatomy  Laboratory WASPADA Semarang for histopatology examination.Result : Prominent abnormality findings on microscopic representation including haemorrhage ptechiae and blood vessel enlargement in almost every organ, meanwhile damaging happened in liver. Microscopic representation examination showed haemorrhage, nekrosis, and inflammation signs.Conclusion : There are prominent abnormality characteristics in macroscopic representation as well as microscopic Wistar Rats organ examination after Warfarin LD-50 and LD-100 administration, most important at liver.